Propriedade intelectual e direitos do consumidor: convergências e descompassos - Freitas, Rodrigo Leme (2015)
The present work has as its scope to take an interconnected approach between the context of the high rate of violation of intellectual property rights and consumer protection. Before entering specifically in the systematical analysis of the spectrum of both juridical institutes, a brief contextualization will be performed regarding the moment called post-modern, based on the assumption that the main subject area does not result from isolated facts, but from a set of factors which echo in the current historical moment. Subsequently, it will be entered in the joint analysis of the two work pillars which are the intellectual property and the consumer right. In a first moment, the main institutes of intellectual property, their foundations and their historical evolution will be analyzed. Then, with regard to the consumer right, the historical movement which resulted in the formation of its structural axis will be studied, as well as the interference of intellectual property in this construction. The objective, regarding these two approaches, is to seek to demonstrate the preliminary convergence line between both juridical institutes, making clear the approximation feature between them. In chapter 5, however, the work ingresses in its second part. The objective will be to bring up some of the practical and theoretical aspects which aid in the clarification of the detachment which was being settled in the analogue study between these two directions, aiming to present, with that, certain dissonances and paradoxes which were being created by virtue of that detachment. In this chapter, therefore, some of the possible unsteadiness generated by this reality will be verified, so that it enables a reflection regarding the paths which have been traced by this context, not only as a matter of systemic coherence, but for an effective protection of the consumer due to the violations generalized to goods protected by intellectual property rights, above all, in peripheral countries such as Brazil